2007
DOI: 10.4103/0973-1482.34685
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of 4-Arylcoumarins from endophytic Streptomyces aureofaciens CMUAc130

Abstract: In a search for antitumor agents, we carried out a screening of 4-arylcoumarins isolated from endophytic Streptomyces aureofaciens CMUAc130, by examining their possible inhibitory effect on the growth of s.c. transplanted Lewis lung carcinoma (LLC) in BDF-1 mice by intraperitoneal (i.p.) administration. The 4-arylcoumarins showed antitumor activity with T/C values of 80.8 and 50.0% at doses of 1 and 10 mg/kg of 5,7-dimethoxy-4-p-methoxylphenylcoumarin treatment, respectively and 81.5 and 44.9% at doses of 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 0 publications
1
24
0
2
Order By: Relevance
“…4-Arylcoumarin analogs from Streptomyces aureofaciens CMUAc130 showed antitumour activity by their inhibitory effects on transplanted LLC in mice. The biochemical mechanisms for the inhibition of tumour proliferation was experimented with adenocarcinoma cell line (A427) for the overexpression of oncoproteins which suggested that 5,7-dimethoxy-4-phenylcoumarin delayed the intracellular signal leading to tumour proliferation (Taechowisan et al 2007). Brartemicin an antibiotic and a novel inhibitor of metastasis produced by Micromonospora sp., was isolated from the Brazilian medicinal plant, Artemisia vulgaris (Igarashi et al 2009).…”
Section: Antitumour and Cytotoxic Compoundsmentioning
confidence: 99%
“…4-Arylcoumarin analogs from Streptomyces aureofaciens CMUAc130 showed antitumour activity by their inhibitory effects on transplanted LLC in mice. The biochemical mechanisms for the inhibition of tumour proliferation was experimented with adenocarcinoma cell line (A427) for the overexpression of oncoproteins which suggested that 5,7-dimethoxy-4-phenylcoumarin delayed the intracellular signal leading to tumour proliferation (Taechowisan et al 2007). Brartemicin an antibiotic and a novel inhibitor of metastasis produced by Micromonospora sp., was isolated from the Brazilian medicinal plant, Artemisia vulgaris (Igarashi et al 2009).…”
Section: Antitumour and Cytotoxic Compoundsmentioning
confidence: 99%
“…A new anti-inflammatory compound, 5, 7-dimethoxy-4-p-methoxylphenylcoumarin (118), and 5, 7dimethoxy-4-phenylcoumarin (119) were isolated from endophytic Streptomyces aureofaciens CMUAc130 [103,104].…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…It is well‐known that coumarins are a versatile class of heterocycles displaying a wide range of therapeutic activities. Particularly, coumarin derivatives have been shown to be pharmacologically useful as anti‐coagulants, anti‐oxidants, antitumorals, free radical scavengers and also anti‐HIV agents …”
Section: Introductionmentioning
confidence: 99%